SYSTEMATIC ANALYSIS OF THE DOMINANT TYPES OF ENTOMOPHAGES IN FRUIT ORCHARDS - U. Rasulova; G. Turdiyeva,; G. Rahmonova; R. Saliyeva; ??.??. ????khmanova; ??.Q. Khamdamov (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2020)
The formation of entomophauna in orchards and their?? development has a great importance, and it greatly influences to the number of phitofags. During our observations of entomophages orchard in agrobiocenosis?? indentified?? 24 dominant types which belong to seven families. Moveover, researches of entomophages show 24 dominant types which belong to 7 families. Besides that we have analysed the share of entomophage varieties concerning the entomophages.